2021
DOI: 10.3389/fnut.2021.701760
|View full text |Cite
|
Sign up to set email alerts
|

NU9056, a KAT 5 Inhibitor, Treatment Alleviates Brain Dysfunction by Inhibiting NLRP3 Inflammasome Activation, Affecting Gut Microbiota, and Derived Metabolites in LPS-Treated Mice

Abstract: Background: The pathogenesis of sepsis-associated encephalopathy (SAE) is complicated, while the efficacy of current treatment technologies is poor. Therefore, the discovery of related targets and the development of new drugs are essential.Methods: A mouse model of SAE was constructed by intraperitoneal injection of lipopolysaccharide (LPS). LPS treatment of microglia was used to build an in vitro model of inflammation. Nine-day survival rates, behavioral testing, transmission electron microscopy (TEM), immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…In previous studies, FMT, probiotics, or certain drugs were shown to alleviate SAE by affecting the intestinal microbiota ( 18 , 24 ). These studies indicated that the gut microbiota may be an upstream regulator of SAE, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, FMT, probiotics, or certain drugs were shown to alleviate SAE by affecting the intestinal microbiota ( 18 , 24 ). These studies indicated that the gut microbiota may be an upstream regulator of SAE, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration changes of these endogenous microflora observed in sepsis lead to the progression of altered mentation and have substantial impacts on CNS function. The reduction in SCFA production from gut microflora during sepsis increases inflammatory markers, endotoxins due to the inability to downregulate inflammation ( 20 ) ( Figure 2 ).…”
Section: The Gut Microbiome In Sepsismentioning
confidence: 99%
“…Limited evidence is now available for the use of prebiotics, probiotics, fecal microbiota transplantation, and Vagus nerve stimulation for the treatment and prevention of SAE. Several investigational therapies demonstrating neuroprotective benefits, including palmitoylethanolamide, KAT5 inhibitors, capsase-1 inhibitors and butyrate supplementation for SAE remain in the therapeutic pipeline ( 20 , 47 , 48 ). Dexmedetomidine exhibits anti-inflammatory effects in vitro and its potential therapeutic benefit in the setting of SAE being actively investigated in the Adjunctive Sedation With Dexmedetomidine for the Prevention of Severe Inflammation and Septic Encephalopathy (ADVISE) trial ( 49 ).…”
Section: Potential Therapeutic Interventions For Sae Targeting the Gu...mentioning
confidence: 99%
“…A recent study conducted by Chen et al found that selective inhibitor of KAT5 histone acetyltransferase (NU9056), an enzyme which is associated with inhibition of the NLRP3 inflammasome, alleviated LPS‐induced cognitive impairment, depressive and anxiety behaviors, and the release of pro‐inflammatory IL‐1β and IL‐18 cytokines in vitro. Also, it also improved BBB permeability and expression of doublecortin (DCX), a marker of newborn neurons, in mouse model of sepsis‐associated encephalopathy (SAE), by inhibiting NLRP3 activity 114 . According to research findings, NU9056 enhanced survivability in animals, ameliorated LPS‐induced cognitive impairment, depression, and anxiety‐like behavior in vivo.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%